2002
DOI: 10.1046/j.1523-5378.2002.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helicobacter pylori on the Development of Vitamin B12 Deficiency in the Absence of Gastric Atrophy

Abstract: The findings provide strong evidence that H. pylori infection is associated with cobalamin deficiency, and show that this is true even in patients with non-ulcer dyspepsia and minimal or no gastric atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 35 publications
2
75
0
2
Order By: Relevance
“…If H. pylori infection has any role in the development or severity of RAS by other mechanisms that we have not investigated in this study, then patients with genetic susceptibility to H. pylori and IL-6 polymorphisms should be evaluated for this infection. H. pylori gastritis, which has been reported by several studies (19,28,29). Low serum cobalamin level and H. Pylori gastritis have been reported to be strongly correlated via mechanisms suggested or reported by authors (18,19).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…If H. pylori infection has any role in the development or severity of RAS by other mechanisms that we have not investigated in this study, then patients with genetic susceptibility to H. pylori and IL-6 polymorphisms should be evaluated for this infection. H. pylori gastritis, which has been reported by several studies (19,28,29). Low serum cobalamin level and H. Pylori gastritis have been reported to be strongly correlated via mechanisms suggested or reported by authors (18,19).…”
Section: Discussionmentioning
confidence: 78%
“…H. pylori gastritis, which has been reported by several studies (19,28,29). Low serum cobalamin level and H. Pylori gastritis have been reported to be strongly correlated via mechanisms suggested or reported by authors (18,19). In addition, several studies of nutritional deficiencies in patients with RAS have reported low levels of serum cobalamin (30,31).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…For example, in patients with dyspepsia, a strong inverse association has been shown to exist between vitamin B 12 levels and H. pylori density, even in those with minimal or no gastric atrophy (Serin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Incidence and baseline of asymptomatically infected population A conclusion regarding the incidence and baseline of an asymptomatically infected population was calculated to be approximately 14.3% (15/105) as represented by the high titer (>15 NTU/mL serum) of anti-H. pylori IgA among normal control subjects aged 18 to 50 years from the Hebron area. In an earlier study by Serin et al (24), 25% of healthy children were PCR-positive for H. pylori (24). Since some of the children were only transiently infected while others may have progressed to become symptomatic (25), it is likely that the percentage of asymptomatic subjects will decrease (i.e.…”
Section: Identification Of Contaminating Variables That Influenced Comentioning
confidence: 98%